2-Methyl 4-quinoline-hydrazide Derivatives as Antitubercular/Antibacterial Agents— Part I - Desai, Pratibha; Patel, Dinesh; Naik, Jiten; Desai, C.M. (Asian Journal of Chemistry, 2010)
Quinoline-hydrazide derivatives were synthesized and screened for theirantibacterial and antitubercular activities.